Granting Exclusive Breastfeeding Certificate to Increase Maternal Motivation for Exclusive Breastfeeding - Nurafifah, Dian; Indah Kartikasari, Ratih; Mauliyah, Ihda; Tri Kusumaningrum, Andri (Journal of Health Sciences, 2022)
The World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) have recommended exclusive breastfeeding, but there are still mothers who do not provide exclusive breastfeeding. In 2018, its number was only 37.3%, while the government's target of exclusive breastfeeding coverage of 80%. One effort to support exclusive breastfeeding mothers is giving certificates. This study aims to determine the correlation between granting exclusive breastfeeding certificates and maternal motivation for exclusive breastfeeding. It was a correlational study with a cross-sectional design. The independent variable was granting exclusive breastfeeding certificates, while the dependent variable was maternal motivation for exclusive breastfeeding. The population was breastfeeding mothers for more than six months in Bedingin Village, Sugio District, Lamongan Regency. The samples were 40 respondents with simple random sampling. We interviewed respondents with a questionnaire as a research instrument. Then, data analysis used the Chi-Square test with α = 0.05. 87.9% of mothers who received exclusive breastfeeding certificates had good motivation for exclusive breastfeeding. In addition, the Chi-Square test obtained p=0.000 (α˂0.05). Thus, there was a significant correlation between granting exclusive breastfeeding certificates and maternal motivation for exclusive breastfeeding. In conclusion, awarding exclusive breastfeeding certificates increase maternal motivation for exclusive breastfeeding. Further, it could improve coverage of exclusive breastfeeding in Indonesia. The local government should make policies in issuing exclusive breastfeeding certificates.